Carotid Artery Stenosis: Comparison of 3D Time-of-Flight MR Angiography and Contrast-Enhanced MR Angiography at 3T - Ivan Platzek; Dominik Sieron; Philipp Wiggermann; Michael Laniado (Radiology Research and Practice)
Purpose. The aim of this study was to assess the correlation of 3D time-of-flight MR angiography (TOF MRA) and contrast-enhanced MR angiography (CEMRA) for carotid artery stenosis evaluation at 3T. Material and Methods. Twenty-three patients (5 f, 18 m; mean age 61 y, age range 45–78 y) with internal carotid artery stenosis detected with ultrasonography were examined on a 3.0T MR system. The MR examination included both 3D TOF MRA and CEMRA of the carotid arteries. MR images were evaluated independently by two board-certified radiologists. Stenosis evaluation was based on a five-point scale. Stenosis grades determined by TOF and CEMRA were compared using Spearman’s rank correlation coefficient and the Wilcoxon test. Cohen’s Kappa was used to evaluate interrater reliability. Results. CEMRA detected stenosis in 24 (52%) of 46 carotids evaluated, while TOF detected stenosis in 27 (59%) of 46 carotids. TOF MRA yielded significantly higher results for stenosis grade in comparison to CEMRA (P=0.014). Interrater agreement was very good for both TOF MRA (κ=0.93) and CEMRA (κ=0.93). Conclusion. At 3T, 3D TOF MRA should not be used as replacement for contrast-enhanced MRA of the carotid arteries, as it results in significantly higher stenosis grades.